Effector Glycosyltransferases in Legionella - Belyi, Yury; Jank, Thomas; Aktories, Klaus (Frontiers in Microbiology, 2011)
Legionella causes severe pneumonia in humans. The pathogen produces an array of effectors, which interfere with host cell functions. Among them are the glucosyltransferases Lgt1, Lgt2 and Lgt3 from L. pneumophila. Lgt1 and Lgt2 are produced predominately in the post-exponential phase of bacterial growth, while synthesis of Lgt3 is induced mainly in the lag-phase before intracellular replication of bacteria starts. Lgt glucosyltransferases are structurally similar to clostridial glucosylating toxins. The enzymes use UDP-glucose as a donor substrate and modify eukaryotic elongation factor eEF1A at serine-53. This modification results in inhibition of protein synthesis and death of target cells. In addition to Lgts, Legionella genomes disclose several genes, coding for effector proteins likely to possess glycosyltransferase activities, including SetA, which influences vesicular trafficking in the yeast model system and displays tropism for late endosomal/lysosomal compartments of mammalian cells. This review mainly discusses recent results on the structure-function relationship of Lgt glucosyltransferases.